2022
DOI: 10.3390/ijerph191912252
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microplastic in the Atmospheric Deposition and How to Identify and Quantify the Threat: Semi-Quantitative Approach Based on Kraków Case Study

Abstract: Airborne microplastic is an emerging and widespread pollutant yet is still under-characterised and insufficiently understood. Detailed description of microplastic air pollution is crucial as it has been identified in human lungs and remote locations, highlighting the atmosphere as a medium of MP dispersion and transportation. The lack of standardization of methods for measuring and further monitoring of microplastic pollution is an obstacle towards assessment of health risks. Since the first recognition of MP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…It can be assumed that the sources of soil contamination with microplastics are comparable to those considered when assessing other environments (e.g., water). Jarosz et al (2022) points out that microplastics tend to aggregate in soils, waters and sediments, which confirms the assumption (Jarosz et al 2022, 11).…”
Section: Sourcessupporting
confidence: 73%
“…It can be assumed that the sources of soil contamination with microplastics are comparable to those considered when assessing other environments (e.g., water). Jarosz et al (2022) points out that microplastics tend to aggregate in soils, waters and sediments, which confirms the assumption (Jarosz et al 2022, 11).…”
Section: Sourcessupporting
confidence: 73%
“…In the direct analysis of MPs in PM filters by Py-GC/MS. small-organic molecules must be addressed; whether by digestion, solvent or acid treatment or thermal extraction. , Studies have shown the utility of thermal extraction clean-up in diverse matrices such as sand, biosolids, rice and blood. …”
Section: Resultsmentioning
confidence: 99%
“…Most of the pyrolysis articles described studies that measured microplastics in matrixes other than air. Only 9 journal articles reported studies using Py-GC/MS to analyze microplastics in air (or airborne) or in the atmosphere. ,, More reliable data comparisons should be possible in the future as Py-GC/MS air studies are expected to increase in frequency and reflect past knowledge of mass, morphology, collection, preparation, and measurement methods, as well as the environmental impact of microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…This last form of classication represents the primary means to quantify MPs and also facilitates subsequent analysis since a part of these microparticles is identied, and the others are evaluated based on similarities. 7 Another way to classify MPs is according to their origin: "primary" and "secondary" MPs. 8 Those MPs that are synthesized at the micrometric scale for multiple applications (such as components of personal care and cleaning products) are called primary MPs.…”
Section: Introductionmentioning
confidence: 99%
“…This last form of classification represents the primary means to quantify MPs and also facilitates subsequent analysis since a part of these microparticles is identified, and the others are evaluated based on similarities. 7…”
Section: Introductionmentioning
confidence: 99%